2016
DOI: 10.1080/21623945.2016.1259778
|View full text |Cite
|
Sign up to set email alerts
|

Habitual physical activity protects against lipopolysaccharide-induced inflammation in mouse adipose tissue

Abstract: Sepsis is a systemic inflammatory response to infection, with no preventative strategies. In this study, we identify a role for habitual physical activity in the prevention of adipose tissue inflammation induced by a model of sepsis, lipopolysaccharide (LPS). Male C57BL/6J mice (8 weeks old) were housed with access to voluntary wheel running (VWR) or sedentary (SED) for 10 weeks. Mice were then injected with LPS (2 mg/kg) or saline (SAL), and tissues were removed 6 hours postinjection. VWR attenuated body, epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 50 publications
2
40
0
5
Order By: Relevance
“…However, even after this statistical adjustment, KO maintained greater levels of visceral WAT Cd8 (an inflammatory T cell marker associated with insulin resistance (Nishimura, et al 2009) gene expression and tended to (P=0.053) maintain greater Tnfa (an inflammatory cytokine known to secreted by inflammatory macrophages and impair adipocyte insulin signaling (Hotamisligil et al 1996)) levels; these findings support that the absence of FGF21 does have adverse inflammatory effects on adipose tissue independent of body weight. While it is likely that the effect of exercise to reduce adipose tissue inflammation was at least somewhat driven by its ability to reduce adiposity, even after the body weight adjustment, exercise-mediated reductions in WAT and BAT Leptin gene expression remained statistically significant, as did the exercise-mediated reduction in WAT macrophage gene expression (i.e., Erm-1 ), confirming previous reports of exercise having direct anti-inflammatory effects in adipose tissue (Castellani et al 2014; Peppler, et al 2017). …”
Section: Discussionsupporting
confidence: 84%
“…However, even after this statistical adjustment, KO maintained greater levels of visceral WAT Cd8 (an inflammatory T cell marker associated with insulin resistance (Nishimura, et al 2009) gene expression and tended to (P=0.053) maintain greater Tnfa (an inflammatory cytokine known to secreted by inflammatory macrophages and impair adipocyte insulin signaling (Hotamisligil et al 1996)) levels; these findings support that the absence of FGF21 does have adverse inflammatory effects on adipose tissue independent of body weight. While it is likely that the effect of exercise to reduce adipose tissue inflammation was at least somewhat driven by its ability to reduce adiposity, even after the body weight adjustment, exercise-mediated reductions in WAT and BAT Leptin gene expression remained statistically significant, as did the exercise-mediated reduction in WAT macrophage gene expression (i.e., Erm-1 ), confirming previous reports of exercise having direct anti-inflammatory effects in adipose tissue (Castellani et al 2014; Peppler, et al 2017). …”
Section: Discussionsupporting
confidence: 84%
“…Indeed, at the protein level, we have recently observed significantly increased PGC‐1 α content in epididymal and inguinal AT depots following 10 weeks of voluntary wheel running (Peppler et al. ).…”
Section: Pgc‐1αmentioning
confidence: 89%
“…While these studies clearly show increased mitochondrial proteins in AT, the extremely strenuous nature of the exercise calls into question the clinical relevance of these findings. However, recent work using forced treadmill running (Xu et al 2011) and voluntary wheel running (Stanford et al 2015;Peppler et al 2016) also report increased mitochondrial proteins in AT.…”
Section: Exercise-induced Mitochondrial Biogenesis In Adipose Tissuementioning
confidence: 99%
“…A great deal of research has attempted to understand the mechanisms behind WAT browning and has identified various endocrine factors that appear to contribute (6, 9, 10). Glucagon has been largely ignored when it comes to adipose tissue metabolism even though the glucagon receptor is present in both eWAT and interscapular BAT (11), and physiologic challenges that cause WAT browning, such as cold exposure (7, 9) and exercise (1, 2, 4), are associated with increased circulating glucagon (1214). Moreover, glucagon can increase whole‐body energy expenditure (EE) (15) and stimulate blood flow and heat production in rodent BAT (16, 17).…”
mentioning
confidence: 99%
“…On the other hand, white adipose tissue (WAT) primarily serves as a sink to store excess calories as triglycerides. Interestingly, subcutaneous inguinal WAT (iWAT) in rodents can transform to a more brownlike phenotype (also known as brite or beige) following cold exposure and exercise (1)(2)(3)(4)(5), among many other stimuli (6). This is distinct from visceral or epididymal WAT (eWAT), which has barely detectable Ucp1 expression in rodents and fails to express a brownlike phenotype even after cold exposure (7,8).…”
mentioning
confidence: 99%